Synthesis of novel Fe3O4 nanostructures surrounded by Ti-MOF nanostructures as bioactive and efficient catalysts in three-component synthesis of new pyrazole derivatives - Qubais Saeed, Balsam; Waleed, Ibrahem; Chlib Alkaaby, Hussein Humedy; Farhan Jawad, Sabrean; Altimari, Usama S.; Ahmed AL-Sarraj, Ziyad Shihab; Shbeeb, Ruwaida T.; Hadrawi, Salema K.; Suliman, Muath; Alshahrani, Mohammad Y. (Frontiers in Materials, 2023)
A one-step, rapid and controllable synthesis of the new Fe3O4 surrounded in Ti-MOF nanostructures was carried out with microwave technology. Product identification with morphology and size distribution technique (SEM), surface area technique (BET), Infrared spectroscopy (FT-IR), Energy-Dispersive X-ray spectroscopy (EDX/EDX mapping), and Vibrating Sample Magnetometer (VSM) were performed. After identifying and confirming the structure, Fe3O4 surrounded in Ti-MOF nanostructures was used as a suitable catalyst with high thermal resistance and recyclable in a three-component reaction of phenylhydrazine, malononitrile and aldehyde to synthesis novel. Synthesized pyrazole derivatives than previously reported methods have less synthesis time and high efficiency. Continuing investigations on Fe3O4 surrounded in Ti-MOF nanostructures, its antimicrobial properties were tested on Gram-positive bacterial species, Gram-negative bacterial species and fungi bacterial, and high effects were observed based on MIC, MBC, and MFC values.